Correspondence of Front-Line Soldiers with Tyumen Residents as a Source on the History of Everyday Life during the Great Patriotic War (1941—1945). - I. V. Skipina (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The 1941—1945 correspondence between servicemen and fellow countrymen, kept in the State Archives of the Tyumen Region is examined in the article. Letters are considered as documents with high information potential, giving new knowledge about the war, obtained on the basis of studying the communications of ordinary participants in the events. The purpose of the publication is to show letters from the front as a source on the history of everyday life, filled with communication of close people on issues important to them, allowing them to reconstruct their life activities, analyze the experience of the past, and use the results of research in modern reality. Correspondence allows us to consider military everyday life as part of big politics and as a personal experience, to expand the source component of the discourse on the history of the Great Patriotic War, contributing to a scientific assessment of the experience and understanding of its historical significance. It is proved that collective and personal letters, appeals “to power” testify that the war, having become a time of difficult trials, stimulated the formation of an identity characterized by the unity of the state and society with the prevalence of socially significant values over individual ones.